Securing Human Rights on the Post-Soviet Space - R. A. Kasyanov; E. A. Torkunova (Vestnik MGIMO-Universiteta)
Abstract: A lot of profound political, economic, social, cultural and legislative modifications have happened on the post-Soviet space since the disintegration of the USSR. The term “post-Soviet space” should not be considered as the geographical boundaries of the fifteen former Soviet republics. The conception of the “post-Soviet space” has a more profound meaning as it reflects the common historical and cultural heritage as well as close economic relations, moreover, friendship between the citizens of the new independent States. The most developed sphere in the interstate relations nowadays is economics. The most prime example is Eurasian Economic Union (EEU), the youngest integration institution in the world which unites five countries willing to construe their relationship on a stronger basis than the proposed format of cooperation within the Commonwealth of the Independent States. In the modern world the economic and financial interests are determining, their ensuring makes the governments change foreign and domestic policies, start and terminate trade wars, desperately fight for the respect of their legal rights or, on the contrary, voluntarily give up on some parts of their sovereignty in the framework of integration development. The experience of the European Union demonstrates that the construction of the unified internal market within which freely move persons, goods, services and capitals is a necessary but not the only attribute of a successful integration project. At a certain moment the complex of economic and financial interests should be supplied with the interests of a concrete person. A strict observation of rights and freedoms is becoming a factor that predetermines a possibility of a conversion to the higher forms of integration. In this article is analyzed the problem of human rights defense in the main organizations functioning on the post-Soviet space - Eurasian Economic Union and Commonwealth of the Independent States.